A Rare Case of Human Asian Trypanosomiasis (a-HT) Due to Trypanosoma evansi - Wabale, Vaishali R. (New Frontiers in Medicine and Medical Research Vol. 9, 2021)
Trypanosoma evansi, the causative agent of Surra, is a hemoflagellate protozoan mechanically transmitted by hematophagous flies, mainly in tropical and subtropical regions. This protozoan affects several mammalian hosts, including dogs, which are highly susceptible to the infection. Trypanosomes are unicellular eukaryotic haemoprotozoan parasite found worldwide. They infect humans, domestic and wild animals and are transmitted by blood-sucking insects. Here, the patient, a pregnant female, in the 28th week, a known case of retroviral disease (RVD) presented with severe anemia and upper respiratory tract infection (URTI) with tuberculous lymphadenitis. Preliminary diagnosis was made was threatened abortion with respiratory tract infection due to complaints of breathlessness on exertion, cough with expectoration, low grade fever since one month along with pain in abdomen and in ear since 15 days. The direct microscopic examination of Leishman stained PBS smear of blood revealed a flagellated form with a purple colored nucleus with a dark red kinetoplast in blue colored cytoplasm and an undulating membrane. A provisional diagnosis of Human Asian Trypanosomiasis (a-HT) was made and confirmed when Trypanosoma evansi grew on Novy- Mac Neal- Nicolle (NNN) Modified Twin pack Medium (HI MEDIA Laboratories, Mumbai). The patient responded to Suramin. Though human serum is lethal to T. evansi, but because the patient was immunocompromised, hence this species led to disease with teaming parasitaemia. This case was an accidental finding during routine OPD and was further studied once we suspected Trypanosomiasis.